Pengaruh Promosi Kesehatan dengan Media Audio Visual terhadap Pengetahuan HIV/AIDS pada Remaja di SMA PGRI 2 Banjarmasin - Era Widia Sary; Elyna Agus Tina; Lukman Harun; Hiryadi Hiryadi; M Syafwani (PPNI UNIMMAN, 2025)
HIV/AIDS is a global health issue that significantly impacts adolescents, a vulnerable group prone to risky behaviors such as unprotected sexual intercourse. The lack of knowledge is a key factor contributing to the increased risk of transmission. Therefore, effective health education interventions are essential to address this problem, with one promising approach being health promotion through audiovisual media. This study aims to assess the impact of audiovisual media on improving HIV/AIDS knowledge among 11th-grade students at SMA PGRI 2 Banjarmasin. The study used a quasi-experimental design with a one-group pretest–posttest approach. The entire population of 112 students was selected using a total sampling technique. The data collection tool was a questionnaire that was tested for validity and reliability. The data were analyzed using the Wilcoxon test, as the data were not normally distributed. Prior to the intervention, most students (85.7%) had low levels of knowledge about HIV/AIDS. Following the intervention, all students (100%) demonstrated a significant increase in knowledge, reaching a high level. The Wilcoxon test yielded a p-value of 0.001 (p<0.05), indicating a statistically significant effect. These findings suggest that audiovisual media is a highly effective method for improving adolescents’ knowledge about HIV/AIDS. It serves as both an engaging and preventive educational strategy, making it an important tool in promoting awareness and reducing the risk of HIV/AIDS transmission among youth.